Plastics in medical devices properties, requirements, and applications - Sastri, Vinod R., 1957- (Elsevier Science, 2013)
Plastics in Medical Devices is a comprehensive overview of the main types of plastics used in medical device applications. It focuses on the applications and properties that are most important in medical device design, such as chemical resistance, sterilization capability and biocompatibility. The roles of additives, stabilizers, and fillers as well as the synthesis and production of polymers are covered and backed up with a wealth of data tables. Since the first edition the rate of advancement of materials technology has been constantly increasing.
Keywords: plasty; polymerní materiály; lékařství; biokompatibilita; biomedicínské inženýrství; plastics; polymer materials; medicine; biocompatibility; biomedical engineering; příručky; elektronické knihy; handbooks, manuals, etc; electronic books